2020
DOI: 10.36849/jdd.2020.5416
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronidase in Dermatology: Uses Beyond Hyaluronic Acid Fillers

Abstract: Hyaluronidase is mostly widely recognized for its off-label use in correction of complications of hyaluronic acid fillers. However, its utility in other aspects of dermatology is less widely acknowledged. We describe the varied uses of hyaluronidase in dermatology and the underlying evidence base for its dermatological indications. This includes its uses in enhancing drug delivery (for local anesthesia, keloid and hypertrophic scars, and for Kaposi's sarcoma), in the treatment of disorders associated with muci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
5
0
2
Order By: Relevance
“…In aesthetic plastic surgery, hyaluronidase is commonly used for over-correction and asymmetry, in which the dose of hyaluronidase is rather diverse and heterogeneous [147]. It is reported that the distribution, amounts, molecular weights and characteristics of HyA in scar tissue are different from those of normal tissue [21,148]. Low-molecular-weight fragments of HyA produced by hyaluronidase are known to stimulate angiogenesis and activate mesenchymal stem cells [144].…”
Section: Hyaluronidasementioning
confidence: 99%
“…In aesthetic plastic surgery, hyaluronidase is commonly used for over-correction and asymmetry, in which the dose of hyaluronidase is rather diverse and heterogeneous [147]. It is reported that the distribution, amounts, molecular weights and characteristics of HyA in scar tissue are different from those of normal tissue [21,148]. Low-molecular-weight fragments of HyA produced by hyaluronidase are known to stimulate angiogenesis and activate mesenchymal stem cells [144].…”
Section: Hyaluronidasementioning
confidence: 99%
“…Nowadays, commercial formulations of exogenous hyaluronidases include purified forms from bovine (BTH) and ovine testicles (OTH) and recombinant human hyaluronidase (rHuPH20) (Searle et al, 2020). Animal derived hyaluronidases are extracted from testis tissue, and are generally purified by series of multiple precipitation, fractionation and filtration steps (Farooqui and Srivastava, 1979;Lyon and Phelps, 1981;Kaya et al, 2015).…”
Section: Hyaluronidases: Adjuvants To Enhance the Diffusion Of Other Drugs And Agents To Correct Esthetic Filling Proceduresmentioning
confidence: 99%
“…Hyaluronidase has been used for retrobulbar, peribulbar, and sub-Tenon's anaesthesia in eye surgery, as a ‘spreading agent’. It reduces tissue oedema, periorbital oedema, and helps re-absorption of subcutaneous hematomas [ 2 , 27 , 28 ]. It assists vitrectomy, that is the surgery of the retina, where vitreous requires removing (the gel-like substance that fills the middle portion of the eye) and replacing it with another solution [ 2 ] by degrading hyaluronic acid into disaccharide compounds and dissociating intercellular substance barrier to liquefy the vitreous [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hyaluronidase has been used to increase the duration and efficacy of anaesthesia; it hydrolysis the HA, increasing connective tissue permeability and collectively leading to a faster anaesthetic effect and a greater anaesthetized surface [ 28 ]. It has been used as an adjunct for inferior alveolar nerve blocks [ 29 ], intra-pulpal anaesthesia [ 30 ], or for craniectomy [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation